Research progress and prospect of medium manganese steel - XU Juan-ping; FU Hao; WANG Zheng; YAN Yu; LI Jin-xu (工程科学学报)
Medium manganese steels with the 3%-12% manganese content have outstanding tensile strength and elongation and low production cost. Thus, they are considered as third-generation advanced high-strength steels for automobiles. The research and development prospects and application potential of medium manganese steel in automotive parts have attracted wide attention both in China and overseas. After the medium manganese is deformed by forging or rolling, heat treatments such as quenching, tempering, and intercritical annealing is performed to obtain metastable austenite and ultra-fine ferrite/martensite microstructures. Metastable austenite transforms to martensite under flow stress, resulting in transformation-induced plasticity (TRIP) effect, which may be accompanied by twinning-induced plasticity (TWIP); the steel consequently exhibits good plasticity without sacrificing strength and thus meets the processing requirement of automobile parts with complex structures. The product of tensile strength and elongation of hot-rolled medium manganese steel, with chemical composition of Fe-0.2C-10Mn-4Al, under quenching and tempering can be larger than 70 GPa·%, which is higher than the current literature value. This paper summarized the current research status of medium manganese steel in China and abroad and analyzed the mechanical properties data of medium manganese steel with different chemical compositions, deformation process, and heat treatment process in the literature. The influence of the chemical composition, deformation process, and heat treatment process on the microstructure and mechanical properties was discussed. The influences of special properties of medium manganese steels, such as lüders band and PLC band, on work hardening rate and hydrogen-induced delayed cracking properties were comprehensively discussed. Moreover, based on deformation control and prediction via the stacking fault energy of the second-generation advanced high-strength steel with pure austenite microstructure, the paper presented a deformation prediction model of the austenite phase in the medium manganese steel. Finally, the paper discussed the problems and prospects of the medium manganese steel.